The impact of the COVID-19 pandemic on forensic pathology services in Limpopo province, South Africa - Thakadu A. Mamashela; Samuel T. Ntuli (South African Family Practice)
Background: To evaluate the effects of coronavirus disease 2019 (COVID-19) and the preventative measures taken, especially how they affect forensic pathology services in rural South Africa.